Association of breast feeding in ovarian malignancy: is breastfeeding a boon? a single institutional experience - Shanmugam , Subbiah; Balakrishnan, Sathiyaseelan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: There are many risk factors which can attribute to ovarian cancer. Oral contraceptive pill (OCP) usage, salpingo-oophorectomy, and high parity are considered as protective factors for ovarian cancer. Lactation (breastfeeding), incomplete pregnancies, and sterilization may offer a weak protection against ovarian cancer. There are only few modifiable risk factors beyond oral contraceptive use exist. Hence identifying additional modifiable factors is needed to tailor prevention strategies. Methods: In our institution, we analyzed 250 patients who underwent treatment for various malignancies from 2020 to 2022. Among those patients, 128 patients were treated for ovarian malignancy who were compared with 122 control patients (patients with malignancy other than ovarian cancer). We collected data of these patients from medical records. We analyzed the association of breast feeding, and the duration of breast feeding with ovarian malignancy. Results: A total of 128 women with ovarian malignancy; mean (SD) age, 53.3 (7.7) years and 122 controls; mean (SD) age, 51.6 (8.0) years were included. Breastfeeding was associated with a 26.4% lower risk of invasive ovarian cancer in patients who breastfed their children for cumulative period of more than one year. Conclusions: Breast feeding is associated with significant reduction in ovarian malignancy when the duration of breast feeding exceeds more than one year. Thus, encouraging breast feeding and increasing the duration of breast feeding may help in reducing the incidence of ovarian malignancy.